The Design of Earthquake Detector Using Pendulum Swing Based on ATMega328 - Prasojo, Ipin; Maseleno, Andino; tanane, Omar; Shahu, Nishith (Universitas Muhammadiyah Yogyakarta, 2021)
Earthquake is a vibrationÂ that occur on the surface of the earth, earthquakes are usually caused by the movement of the earth's crust (earth's plates). Earthquakes are also used to indicate the area from which the earthquake occurred. Even though our earth is solid, it always moves and earthquakes occur when the pressure caused by that movement is too large to be able to withstand. One of the effects of the earthquake vibration itself that reaches the earth's surface and if the vibration is large enough can damage buildings and other infrastructure such as roads and bridges, railroad tracks, dams and others, causing casualties and property losses. So that we can avoid the danger caused by an earthquake, it is necessary to design an earthquake detection device with a pendulum swing method based on the ATMega328 Microcontroller. The ATMega328 microcontroller is the core of all the systems that exist in this design. In the design of earthquake measuring device using infrared sensors and photodiodes. Where the infrared beam construction is determined by the pendulum which detects the swing.